SLOW TOURISM AS A CONTEMPORARY TENDENCY IN THE TOURISM MARKET: IMAGE CONTENT AND GEOTAG ANALYSIS ON INSTAGRAM - Lazarević, Sonja; Stanišić, Tanja; Andreea Ion, Raluca (Economics of Agriculture, 2024)
Although it originated from the Slow Food and Cittaslow movements, slow tourism has spread to many spheres of tourism. The purpose of the paper is to investigate what people associate with slow tourism, and how and where they engage in slow tourism. Social media content analysis on Instagram, using hashtag #slowtourism, was performed in the research. The general conclusion is that people mostly associate slow tourism with different forms of architecture and landscape, and to lesser extent with transport and food. Also, there was significant content variation within the architecture and landscape categories, suggesting that people associate different types of architecture and tourism destinations with slow tourism. When it comes to location, the majority of photos were taken in Italy, which is not surprising, considering that Slow Food and Cittaslow movements originated in this country.